PRESENTING ANIMATION MOVIES IN TEACHING WRITING - Syam, Anugerah Febrian; Efendi, Rahman (Fakultas Keguruan dan Ilmu Pendidikan, 2016)
This present study aimed at finding out the possible improvement of students’ writing skill through animation movie. Animation movie was used as media in the class. Classroom action research that consisted of three cycles was applied in this study. The data were collected through three meetings of cycle 1 and two meetings for each Cycle II and III. This study was held in SMA Negeri 8 Bulukumba (a Model School of Bulukumba). The result of the study shows that animation movies could easily improve the students’ skill in writing narrative text. The study indicated that there was the significant improvement of the students’ writing skill through animation movie. Conclusion based on the result analysis shows that the use of Animation Movie can improve writing skill at the tenth-grade students of SMA Negeri 8 Bulukumba.